2022
DOI: 10.1021/acsanm.2c01136
|View full text |Cite
|
Sign up to set email alerts
|

Mild Liquid-Phase Exfoliation of Transition Metal Dichalcogenide Nanosheets for Hydrogen Evolution

Abstract: Developing a general strategy to efficiently exfoliate transition metal dichalcogenide (TMD) electrocatalysts would be significantly beneficial for the electrocatalytic hydrogen evolution reaction (HER) from water splitting. However, there are several challenges in the production of two-dimensional (2D) TMDs, including the complicated fabrication process, high defect rate, and low production yield. Herein, we developed a general applicable mild organic molecular intercalator-assisted liquid-phase exfoliation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…In LPE approach, the bulk MoS 2 is inserted in an aqueous surfactant solution followed by sonication to separate the atomic layers. 136,137 This technique is used for the synthesis of large quantities and high quality 2D MoS 2 . LPE has good electrochemical and electron transfer ability; because of this the MoS 2 films grown by this method are mostly preferred for electrochemical storage, catalysis and sensing applications.…”
Section: Mechanical Exfoliation (Me)mentioning
confidence: 99%
“…In LPE approach, the bulk MoS 2 is inserted in an aqueous surfactant solution followed by sonication to separate the atomic layers. 136,137 This technique is used for the synthesis of large quantities and high quality 2D MoS 2 . LPE has good electrochemical and electron transfer ability; because of this the MoS 2 films grown by this method are mostly preferred for electrochemical storage, catalysis and sensing applications.…”
Section: Mechanical Exfoliation (Me)mentioning
confidence: 99%
“…Intercalation LPE is another representative top-down way for the production of 2D p-type MCs [63,[66][67][68]. The basic strategy of this method is to intercalate molecules such as ions or organic molecules into layered bulk crystals, which could expand the interlayer distance of bulk material and waken the vdW interaction between layers [45].…”
Section: Liquid Phase Exfoliationmentioning
confidence: 99%
“…Ambrosi et al successfully exfoliated 2D WSe 2 by using tert-butyllithium as an intercalant [67]. In addition, some organic molecules are also explored for the mild exfoliation of 2D p-type MCs [66]. Zhang et al reported the exfoliation of WSe 2 via mild intercalation LPE [66].…”
Section: Liquid Phase Exfoliationmentioning
confidence: 99%
See 1 more Smart Citation
“…The device exhibited good photoresponse performance and bending−folding stability and has great application potential in the field of flexible optoelectronic devices. 22,23 The bulk Gr 2 Ge 2 Te 6 crystals were added to the triturator and milled for 30 min to make the bulk crystals into powder. In quick succession, the collected Gr 2 Ge 2 Te 6 crystal powders were uniformly dispersed into N-methylpyrrolidone (NMP) solution, in which NMP served as a dispersant and acted as a barrier to air and moisture.…”
Section: Introductionmentioning
confidence: 99%